Dinitrogen activation on graphene anchored single atom catalysts: local site activity or surface phenomena - Maibam, Ashakiran; Govindaraja, Thillai; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2019)
Catalysis on two-dimensional (2D) substrates with metal clusters or centers is generally dealt with as a surface phenomenon under the conjecture that the delocalized electron density is the driving force. When single atom catalysts (SACs) are anchored on such materials with delocalized electron density, for instance graphene, the stimulant for catalysis may be either the d-electrons on the metal or the system altogether. To understand the contributing factors of catalysis on such systems, a case study of dinitrogen (N-2) activation on Mo anchored graphene has been made by employing periodic and finite models of graphene. The periodic model represents a continuum of SACs anchored periodically on graphene, while the finite models are graphene nanoflakes of varying sizes and edge orientations. In addition to the physical aspects, such as size/finiteness of graphene, the influence of varying chemical compositions of the substrate on the activity is also evaluated by doping graphene with different B and N concentrations. This study, while clearly bringing out the connotation of regulating atomic composition of graphene substrate for dinitrogen activation, also surprisingly unveils the relative insignificance of varying the size and edge effects of the substrate. These features are highlighted through an analysis of red shift in the N-N stretching frequency, charge transfer to dinitrogen from the catalytic system, and structural and electronic characteristics of the catalytic system. The total and projected density of states plots reveal hybridization between the metal d orbitals and the p orbitals of carbon and nitrogen in the valence band. On the other hand, the frontier molecular orbital analysis also depicts a strong chemisorption of dinitrogen with the metal-graphene supports on account of direct hybridization between the d orbitals of the supported metal atom and the p orbitals of dinitrogen. The Bader and Lowdin charge distribution on the adsorbed dinitrogen in periodic and finite models shows the preeminence of local site over the surface activity.

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting

Doped 2D VX2 (X = S, Se, Te) monolayers as electrocatalysts for ammonia production: a DFT based study - Maibam, Ashakiran; BabaRao, Ravichandar; Krishnamurty, Sailaj A. (Applied Surface Science, 2022)
Electrocatalytic nitrogen fixation under ambient conditions on vanadium dichalcogenides (VX2) with non-metal dopants has been explored herein. Understanding the interface chemistry, inherent electronic and acute synergistic nature of non-metal dopants on two unique phases of VX2 has been meticulously explored through a scrutiny of several non-metal atoms as catalytic centers. The efficacity of N-2 chemisorption and N-N bond activation has been implemented as crucial parameters to realize boron and carbon doped VX2 monolayers to be electrocatalytically active for nitrogen reduction reaction (NRR). Detailed investigation on the NRR mechanism brings out the pivotal role of thermodynamic favourability for product formation obtained from Gibbs free energy differences. The charge transfer on N and pi-pi* orbital hybridization and electron ``donor-acceptor `` mechanism between the non-metal and N-2 has been found to modulate the electrocatalytic barrier for NRR on VX2 monolayers. This study proposes boron doped VS2 as an efficient chemically feasible, earth abundant sustainable electrocatalyst for NRR with an overpotential as low as 0.06 eV.
Keywords: 1T and 2H phases; DFT; electrocatalysts; Nitrogen Reduction Reaction; Non metal dopants; Vanadium dichalcogenides

D-A-D-based unsymmetrical thiosquaraine dye for the dye-sensitized solar cells(dagger) - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemistry and Photobiology, 2023)
In dye-sensitized solar cell, modulating the electronic properties of the sensitizer by varying the donor, pi-spacer, acceptor and anchoring groups help optimizing the structure of the dye for better device performance. Here, a donor-acceptor-donor-based unsymmetrical thiosquaraine sensitizer (SQ5S) has been designed and synthesized. Photophysical, electrochemical, theoretical and photovoltaic characterizations of SQ5S dye have been compared with its oxygen analog, SQ5. The incorporation of the sulfur atom in the acceptor unit of SQ5S dye showed an intense peak at 688 nm, which was 38 nm of red-shifted and showed the panchromatic light harvesting response with the onset of 850 nm compared with SQ5 dye. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of electrolyte for the charge injection and the dye-regeneration processes, respectively. Photovoltaic efficiency of 1.51% (V-OC 610 mV, J(SC) 3.07 mA cm(-2), ff 81%) has been achieved for SQ5S dye, whereas SQ5 showed the device performance of 5.43% (V-OC 723 mV, J(SC) 9.3 mA cm(-2), ff 80%). The decreased device performance for the dye SQ5S has been attributed to the favorable intersystem crossing process associated with the photoexcited SQ5S that reduces the driving force for the charge injection process.